ARTventure: learning Malay traditional dance through Augmented Reality / Muhammad Fahmi Rusli and Nor Intan Shafini Nasaruddin - Rusli, Muhammad Fahmi; Nasaruddin, Nor Intan Shafini (Faculty of Computer and Mathematical Sciences, 2023)
Malaysia's traditional dances exemplify the nation's rich multicultural identity, a source of worldwide renown. Among these, Malay folk dances stand out, embracing diverse cultural practices like martial arts, storytelling, and humour. To ensure the preservation of this cultural heritage and ignite interest among the younger generation, effective materials are crucial. Enter an innovative augmented reality, this based learning application focused on the Inang dance, employing marker-based AR technology. This application holds the potential to safeguard Malay traditional dance among the youth, particularly students. Moreover, it fosters curiosity, inspiring users to delve deeper into the world of performing arts. Rooted in the ADDIE model, a proven and adaptable learning methodology, this project paves the way for future learning models to thrive, ensuring the legacy of Malaysia's traditional dances endures. For future recommendations, the application should offer comprehensive learning opportunities for Malay Dance enthusiasts. It must serve as a valuable resource for learning dance intricacies, acting as both a revision tool for experienced dancers and an attraction for newcomers to explore the culture. Additionally, attention to detail in animations is vital for creating immersive and captivating learning experiences. Expanding compatibility to multiple platforms will broaden the audience and promote the beauty of Malay Dance. The engagement testing yielded promising results and analysis, showcasing a favourable overall percentage of 72.71%. Despite encountering specific project limitations, these obstacles provide valuable lessons and serve as a compass for guiding future enhancements in application development. Through these enhancements, the augmented reality-based Malay Dance application can transform into a potent force, championing the promotion and preservation of this exquisite art form and its heritage. Simultaneously, it will entice users to embark on an alluring expedition, immersing themselves in the diverse and captivating cultural tapestry